Peran Dinas Lingkungan Hidup dalam Pengendalian Pencemaran Lingkungan akibat Limbah Pabrik Kelapa Sawit di Kabupaten Kampar - Lulu Erawan; Nur Meilani (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Environmental pollution due to palm oil mill waste is a serious issue in Kampar Regency, impacting river water quality, public health, and ecosystem sustainability. As a technical agency, the Kampar Regency Environmental Agency is responsible for controlling pollution that support environmental management. This study aims to analyze the role of the Environmental Service and the factors that influence it in controlling environmental pollution due to palm oil mill waste in Kampar Regency. This study uses a descriptive qualitative research type. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and conclusion drawing/verification. The theory used is the role of public sector organizations according to Jones (in Mahsun, 2013), namely regulatory role, enabling role, and direct provision of goods and services. The results of the study indicate that the Environmental Agency has carried out these three roles, but the implementation has not been optimal. Regulations have been established, a complaint mechanism is in place, and technical services are provided. However, community involvement is low, and physical mitigation facilities are not yet available. Improved transparency, cross-stakeholder coordination, provision of supporting facilities, and active community participation are needed to optimize the Environmental Agency's role in controlling environmental pollution caused by palm oil mill waste in Kampar Regency.